2021
DOI: 10.17159/sajs.2021/8035
|View full text |Cite
|
Sign up to set email alerts
|

Estimating lightning NOx production over South Africa

Abstract: Nitrogen oxides (NOx = NO + NO2) are toxic air pollutants and play a significant role in tropospheric chemistry. Global NOx hotspots are the industrialised regions of the USA, Europe, Middle East, East Asia and eastern parts of South Africa. Lightning is one of the many natural and anthropogenic sources of NOx to the troposphere. It plays a role in the formation of particulate matter and tropospheric ozone, which are both linked to harmful health and climate effects. The discourse on NOx over the southern Afri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…S5 in the Supplement) compared to a standard CAM-chem simulation (not shown); therefore, the high ozone in the upper troposphere may be due to an overestimate of lightning NO. We also compared our modeled lightning NO emissions with a multi-year average climatology (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) from Maseko et al (2021) over Southern Africa and found that the seasonal cycles from MU-SICAv0 and standard CAM-chem are consistent with the climatology. The magnitude of MUSICAv0 lightning NO emissions agree better overall with the climatology compared to that from standard CAM-chem simulation.…”
Section: Western Africamentioning
confidence: 85%
“…S5 in the Supplement) compared to a standard CAM-chem simulation (not shown); therefore, the high ozone in the upper troposphere may be due to an overestimate of lightning NO. We also compared our modeled lightning NO emissions with a multi-year average climatology (2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) from Maseko et al (2021) over Southern Africa and found that the seasonal cycles from MU-SICAv0 and standard CAM-chem are consistent with the climatology. The magnitude of MUSICAv0 lightning NO emissions agree better overall with the climatology compared to that from standard CAM-chem simulation.…”
Section: Western Africamentioning
confidence: 85%
“…Additionally, the IC/CG flash ratio may vary during a thunderstorm [16]. In South Africa, the estimated IC/CG ratio value is 3:1 -the most commonly used ratio for the mid-latitude region [17].…”
Section: Introductionmentioning
confidence: 99%